Research on Allelopathy: Potential Wild Plant Species in Vietnam - Men, Tran Thanh (Recent Progress in Plant and Soil Research Vol. 3, 2021)
Allelopathy is a common biological phenomenon happened when an allelopathic plant produces allelochemicals that positively or negatively affect the growth, survival, development, and reproduction of other plant species nearby in the same ecosystem. Wild plants are known as plants that are available in nature in large quantities, with the ability to reproduce quickly and many biologically active substances. Many studies have shown that wild plants are capable of synthesizing many allelochemicals. Wild plant species such as Mimosa pigra L., Leucaena leucocephala (Lamk.) de Wit., Wedelia trilobata (L.) Hitchc, Leucaena glauca Benth and Ageratum conyzoides L. are common in Vietnam and invade most cultivated land areas, affecting the productivity and growth of the surrounding crops. This review was based on the ability to inhibit weed species of some wild plants to identify the potential plants containing biologically active substances or compounds for herbicides with biosafety for agro-ecosystems.